1982
DOI: 10.3109/01485018208990207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Panax Ginseng on Testosterone Level and Prostate in Male Rats

Abstract: Adult male rats were treated with 1% and 5% Panax Ginseng in their diet for 60 days. Control rats were used. There was an increase in daily food consumption without an increase in body weight of treated animals. Rats that received 5% ginseng experienced a significant increase in blood testosterone level (p < 0.001). Prostate weight in the treated animals was significantly reduced as compared to the control animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 3 publications
4
28
1
Order By: Relevance
“…Moreover, KRG-WE was more effective than crude saponin in improving various parameters related to spermatogenesis, such as the Johnsen's score, seminiferous tubular size, percentage of tubules containing sperm, sperm count, and germ cell count. KRG-WE significantly improved the FSH and LH levels (p<0.05) ( Table 3) and increased testosterone levels in old rats (p<0.01), consistent with an earlier report [33]. The agerelated decline of Leydig cell steroidogenesis has potential implications for the decline of male fertility, and high testicular testosterone concentrations are required to maintain spermatogenesis [34].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, KRG-WE was more effective than crude saponin in improving various parameters related to spermatogenesis, such as the Johnsen's score, seminiferous tubular size, percentage of tubules containing sperm, sperm count, and germ cell count. KRG-WE significantly improved the FSH and LH levels (p<0.05) ( Table 3) and increased testosterone levels in old rats (p<0.01), consistent with an earlier report [33]. The agerelated decline of Leydig cell steroidogenesis has potential implications for the decline of male fertility, and high testicular testosterone concentrations are required to maintain spermatogenesis [34].…”
Section: Discussionsupporting
confidence: 77%
“…These positive aphrodisiac effects of ginseng may be attributed to the enhancement of nitric oxide release from endothelial cells of penile corpus cavernosum and consequent relaxation (122). Furthermore, Fahim et al (123) and Bahrke and Morgan (124) reported that Panax ginseng produced a dose-related increase in serum testosterone levels and American ginseng reduced the plasma level of prolactin hormone in rats. Testosterone might mediate the heightened copulatory behavior in ginseng-treated animals, while prolactin altered it.…”
Section: Aphrodisiac Effect Of Ginsengmentioning
confidence: 95%
“…Rats treated with 5% Panax Ginseng in their diet for 60 days experienced a significant increase in blood testosterone level [46]. Research has also shown that Panax ginseng enhances the libido possibly through its effects on the CNS and gonadal tissues, as well as by increasing stamina during intercourse [110].…”
Section: Non-herbal Dietary Supplementsmentioning
confidence: 97%
“…We are presently completing a study in our lab involving DAA supplementation, which should provide additional evidence for or against the use of this amino acid for purposes of testosterone elevation. [41][42][43], ginkgo biloba [44,45], ginseng [46,47], passionflower extract (passiflora incarnate) [22,40,101], Longjack root (eurycoma longifolia) [38,39,102], and tribulus terrestris [17,24,48] are all touted to have health benefits and to increase testosterone levels. Of these, Longjack root and tribulus terrestris are of particular interest in the research community and will be explored in greater detail throughout the remainder of this review.…”
Section: Nutrient Intakementioning
confidence: 99%
See 1 more Smart Citation